2014
DOI: 10.5799/ahinjs.02.2014.02.0128
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistant Staphylococcus aureus nasal colonization among secondary school students at Duhok City-Iraq

Abstract: Objective: Methicillin-resistant Staphylococcus aureus (MRSA) widely distributed in hospitals around the world. There is strong relationship between disease development and S. aureus nasal carriage. The aim of this study was to evaluate the prevalence and epidemiology of nasal colonization with S. aureus and MRSA in the community of Duhok city, Iraq.Methods: 489 students aged 16 to18 years were included. Nasal swab samples were collected followed by antimicrobial susceptibility test. MRSA isolates were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 27 publications
6
36
11
Order By: Relevance
“…The exact cause for this is unknown, but it was thought to be due to elimination of pop off mechanism. UTI is a common problem in our region and is caused by multi-drug resistant microorganisms (8,29). Such an infection can predispose to septicaesmia and renal scaring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact cause for this is unknown, but it was thought to be due to elimination of pop off mechanism. UTI is a common problem in our region and is caused by multi-drug resistant microorganisms (8,29). Such an infection can predispose to septicaesmia and renal scaring.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent VUR related sequels, participants can be treated by continuous antibiotic prophylaxis, surgical intervention by ureteric reimplantation, or endoscopic treatment by injecting bulking agents (7). Continuous antibiotic prophylaxis might be associated with increased levels of resistance (8) and antibiotics-related side effects. Therefore, many studies have recommended surgical intervention and particularly endoscopic treatment as the first line of management (9-15).…”
Section: Introductionmentioning
confidence: 99%
“…E. coli and other genera of gram negative bacteria possess a naturally occurring, chromosomally mediated β-lactamase and plasmid mediated β-lactamase [8]. The antibiotic misuse, ineffective empiric antibiotic therapy, poor dosing, prolonged antibiotic treatment and spontaneous use of these antibiotics in developing countries are the reason for the development of high resistance rates in bacterial isolates [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in the UK, the UTI rate was found to be higher in transplanted kidneys with stent than those without stent (10). Recalling that multidrug resistant microorganisms are common in Iraq, infection poses a deleterious effect on the graft (7,(11)(12)(13)(14). In our study, we found that 29.4% of our stented patients versus 7.4% of the non-stented patients developed UTI within the first two weeks after transplant.…”
Section: Discussionmentioning
confidence: 99%